Effects of combat training on visuomotor performance in children aged 9 to 12 years - an eye-tracking study - Yan-Ying Ju; Yen-Hsiu Liu; Chih-Hsiu Cheng; Yu-Lung Lee; Shih-Tsung Chang; Chi-Chin Sun; Hsin-Yi Kathy Cheng (BMC, 2018)
Abstract Background Data on visuomotor performance in combat training and the effects of combat training on visuomotor performance are limited. This study aimed to investigate the effects of a specially designed combat sports (CS) training program on the visuomotor performance levels of children. Methods A pre-post comparative design was implemented. A total of 26 students aged 9-12 years underwent 40-min CS training sessions twice a week for 8 weeks during their physical education classes. The CS training program was designed by a karate coach and a motor control specialist. The other 30 students continued their regular activities and were considered as a control group. Each student's eye movement was monitored using an eye tracker, whereas the motor performance was measured using a target hitting system with a program-controlled microprocessor. The measurements were taken 8 weeks before (baseline), 1 day before (pretest), and 1 week after (posttest) the designated training program. The task used for evaluating these students was hitting or tracking random illuminated targets as rapidly as possible. A two-way analysis of variance [group(2) × time(3)] with repeated measures of time was performed for statistical analysis. Results For the children who received combat training, although the eye response improvement was not significant, both the primary and secondary saccade onset latencies were significantly earlier compared to the children without combat training. Both groups of students exhibited improvement in their hit response times during the target hitting tasks. Conclusion The current finding supported the notion that sports training efforts essentially enhance visuomotor function in children aged 9-12 years, and combat training facilitates an earlier secondary saccade onset.